2010
DOI: 10.1209/0295-5075/92/38001
|View full text |Cite
|
Sign up to set email alerts
|

Speed of crack propagation in dry aqueous foam

Abstract: Applying pressure driving to a single layer of aqueous foam bubbles induces a void propagation that is a surprisingly close analog of dynamic crack propagation. Depending on the rate of applied stress, both a ductile and a brittle mode of propagation are observed, the latter at much higher propagation speeds. A pronounced velocity gap is found, with a well-defined upper limit to the ductile crack speed and a well-defined lower limit to the brittle propagation speed. Both limits can be quantitatively explained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
34
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 29 publications
11
34
0
Order By: Relevance
“…Consistently with [1], we have also found that the fragile cracks do not propagate slower than a certain velocity. To measure such a minimal velocity, we have considered experiments where a spontaneous fragile-ductile transition occurs, as considered also in [15]; we then take the displacement of the crack tip between the two images in the fragile regime closest to the transition as an estimate of the minimal velocity of fragile propagation v min .…”
Section: Minimal Velocity In the Fragile Regimesupporting
confidence: 89%
See 4 more Smart Citations
“…Consistently with [1], we have also found that the fragile cracks do not propagate slower than a certain velocity. To measure such a minimal velocity, we have considered experiments where a spontaneous fragile-ductile transition occurs, as considered also in [15]; we then take the displacement of the crack tip between the two images in the fragile regime closest to the transition as an estimate of the minimal velocity of fragile propagation v min .…”
Section: Minimal Velocity In the Fragile Regimesupporting
confidence: 89%
“…The injection rate is quantitatively captured by a simple model balancing the air overpressure with known foam/wall friction laws for incompressible interfaces. We also revisit the critical velocity criteria for the injected air proposed by Arif et al [1]. The upper bound of velocity in the ductile regime, based on the resistance of soap films against wall friction, is shown to hold much better for mobile than for incompressible interfaces.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations